Transforming a fragmented South African society through a spirituality of koinonia coram Deo - Knoetze, JJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2014)
Spirituality is a way of living. It is described as that which touches the core of human existence, namely “our relationship to the Absolute”, whatever the definition of the latter may be. In this paper, we deal with the importance of our relationship with the Trinitarian God as revealed in Scripture and determined by Christ. The world experiences a revolution in secular spirituality, rejecting a dualistic supernaturalism. This paper will not try to cover the whole debate and spectrum of spirituality, but will focus mainly on the most obvious spiritualities in the South African society, namely Biblical, post-modern and African spirituality. It is the argument of this paper that transforming and liberating spirituality will have to take the influence of sin on our koinonia with God and with our neighbour seriously. The importance of the different dimensions of koinonia as inner dynamics of the process of transformation and liberation will help dispel the myth that Christian spirituality has no relevance in a socio-political situation.